Vitamin D Deficiency and Chronic Lung Disease - Christopher R Gilbert; Seth M Arum; Cecilia M Smith (Canadian Respiratory Journal)
Vitamin D deficiency is increasingly being recognized as a prevalent problem in the general population. Patients with chronic lung diseases such as asthma, cystic fibrosis, chronic obstructive lung disease and interstitial pneumonia appear to be at increased risk for vitamin D deficiency for reasons that are not clear.